2006
DOI: 10.1097/01.qai.0000174657.71276.9f
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal HIV Counseling and Rapid Testing in Tijuana, Baja California, Mexico

Abstract: These findings indicate a wide acceptance of HIV counseling and testing and document a higher HIV seroprevalence among pregnant women delivering at Tijuana General Hospital than current established estimates in Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 19 publications
2
36
2
1
Order By: Relevance
“…3 Among 1,064 women in labor in Tijuana, HIV prevalence was 1.1% overall, G1% among non-drug using women and 6% among women using drugs or whose partners were users. 3 These data are in stark contrast to earlier studies that found HIV prevalence to be 0.09% in pregnant women and 0.3% in the general adult population and suggest that HIV prevalence may be increasing among highrisk Tijuana subpopulations. 5 In light of these recent data and a lack of more comprehensive epidemiological surveillance, the purpose of this study was to estimate the current number of adult men and women infected with HIV in Tijuana.…”
Section: Introductioncontrasting
confidence: 79%
See 2 more Smart Citations
“…3 Among 1,064 women in labor in Tijuana, HIV prevalence was 1.1% overall, G1% among non-drug using women and 6% among women using drugs or whose partners were users. 3 These data are in stark contrast to earlier studies that found HIV prevalence to be 0.09% in pregnant women and 0.3% in the general adult population and suggest that HIV prevalence may be increasing among highrisk Tijuana subpopulations. 5 In light of these recent data and a lack of more comprehensive epidemiological surveillance, the purpose of this study was to estimate the current number of adult men and women infected with HIV in Tijuana.…”
Section: Introductioncontrasting
confidence: 79%
“…2 This was combined with local HIV and behavior data to derive the number of high-risk pregnant women. 2,3 HIV prevalence estimates for Tijuana were based on a variety of serosurveillance and community based seroprevalence studies (Table 2). High and low estimates of HIV-infected MSM were obtained from published local survey results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Our rate of HIV infection is lower than that reported both from the 2004 study in antenatal clinics in Tijuana, Mexico 15 and from the 2001 study in antenatal clinics in Vitória, Brazil.…”
Section: Discussioncontrasting
confidence: 52%
“…Juarez have implications for the transmission of blood-borne infections such as HIV and viral hepatitis. HIV prevalence among IDUs and other high-risk groups in Mexico has thus far remained low (UNAIDS, 2002), but a seroprevalence study of pregnant women in Tijuana observed an HIV prevalence of 1.1% overall; 0% among non-drug using women and 6% among those admitting injection drug use (Viani et al, 2006). Mexican and border health officials have expressed concern that these data represent a looming HIV epidemic linked to drug use.…”
Section: Introductionmentioning
confidence: 99%